Undescribed ecdysteroids and phenolic glycosides from the roots of Cyathula officinalis Kuan and their anti-inflammatory activity in LPS-induced RAW 264.7 macrophages in vitro. (April 2022) - Yang, Long-fei; Teng, Li; Huang, Yue-hui; Tang, Min; Liao, Wan; Fu, Qiang
Abstract: Six undescribed compounds, including four undescribed ecdysteroids (cyathsterones A-D) and two undescribed phenolic glycosides (cyathglucosides A-B), were isolated from the roots of Cyathula officinalis Kuan. Their structures were based on chemical analyses, NMR spectroscopic evidence, DP4+ calculations, and hydrolysis products. All compounds inhibited NO release in lipopolysaccharide (LPS)-induced RAW 264.7 macrophages in vitro . Among them, cyathsterone A showed the strongest inhibitory effects. Moreover, cyathsterone A has been shown to inhibit the release of the proinflammatory cytokines TNF-α, IL-6, and IL-1β in LPS-induced RAW 264.7 macrophages in vitro . Further studies found that cyathsterone A present concentration-dependent suppression of the protein expression of iNOS and COX-2 in LPS-stimulated RAW 264.7 cells in vitro and exerted anti-inflammatory activity via the NF-κB signalling pathway. Graphical abstract: Image 1 Highlights: Six undescribed compounds were isolated from the roots of Cyathula officinalis Kuan. Their structures were elucidated by various spectroscopic techniques. Compounds 1 –6 showed inhibitory effects against nitric oxide. Compound 1 exerted anti-inflammatory activity via the NF-κB signalling pathway.